2018
DOI: 10.1002/ijop.12499
|View full text |Cite
|
Sign up to set email alerts
|

Family socioeconomic status and emotional adaptation among rural‐to‐urban migrant adolescents in China: The moderating roles of adolescent's resilience and parental positive emotion

Abstract: Low family socioeconomic status (SES) is closely related to increased risk of emotional maladaptation among adolescents. Although previous studies have found that low family SES is a significant and common experience for most rural-to-urban migrant adolescents in China, little research has examined the association between family SES and emotional adaptation or identified the protective factors that may minimise emotional maladaptation among these adolescents. The present study examined the associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
(45 reference statements)
2
10
0
Order By: Relevance
“…Specifically, in the context of higher levels of peer support, higher levels of resilience were found to enhance self-esteem. This pattern is congruent with previous research that higher levels of resilience interact with family resources to explain emotional adaption in rural-to-urban migrants 41. Also, our findings confirmed a risk and resilience perspective that the interaction between social contexts and personal traits can explain the variation in positive psychosocial adjustment 7.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, in the context of higher levels of peer support, higher levels of resilience were found to enhance self-esteem. This pattern is congruent with previous research that higher levels of resilience interact with family resources to explain emotional adaption in rural-to-urban migrants 41. Also, our findings confirmed a risk and resilience perspective that the interaction between social contexts and personal traits can explain the variation in positive psychosocial adjustment 7.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, interventions aimed at reducing migrant girls’ stressful life events are important, given that more stressful life events may increase the level of depression, which could make them vulnerable to engaging in NSSI. Secondly, previous studies showed that an intervention designed to enhance resilience could facilitate protective factors among children with stress (Huang, Han, Sun, Zhang, & Li, 2019; Ye et al, 2016); therefore, resilience‐based interventions in school, designed for migrant children with high levels of stressful life events, may help them improve the ability to cope with daily stress, which, in turn, breaks the link between stressful life events and depressive symptoms. Thirdly, equipping migrant girls with alternative, healthy strategies to manage emotions may be an effective way to prevent them from using NSSI to cope with depressive emotions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, parental confidence in the future of an adolescent may infuse them with high hopes, optimism, and a sense of direction, which further promotes their positive adaption during stressful situations (Gao et al, 2020 ). However, research has found that Chinese parents with low SES are typically so busy working that they seldom communicate with their children (Huang et al, 2019 ). In addition, research shows that parents with a low family SES adopt more overprotective parenting styles (Hoffman, 2003 ; Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%